A Five-Year Follow-Up on the Role of Educational Support in Preventing Dropout From Upper Secondary Education in Finland. (July 2015) - Hakkarainen, Airi M.; Holopainen, Leena K.; Savolainen, Hannu K.
In this longitudinal study, we investigated the role of word reading and mathematical difficulties measured in 9th grade as factors for receiving educational support for learning in upper secondary education in Grades 10 to 12 (from ages 16 to 19) and furthermore as predictors of dropout from upper secondary education within 5 years after compulsory education. In addition, we studied the role of school achievement in Grades 9 and 11 in this prediction. The participants of this study were members of one age group of 16-year-old ninth graders ( N = 595, females 302, males 293) in a midsized Finnish city, who were followed for 5 years after completing compulsory education. The path model results, where the effects of gender, educational track, and SES were controlled, showed, first, that students with academic learning difficulties received educational support for learning particularly in the 11th grade. Second, academic learning difficulties directly affected school achievement in the 9th grade, but no longer in the 11th grade. Third, mathematical difficulties directly predicted dropout from upper secondary education, and difficulties in both word reading and mathematics had an indirect effect through school achievement in Grades 9 and 11 on dropout.